Full-wave rectification of a low-voltage source - Torla, Ahmad Lutfi; Khan, Sheroz; Abdul Muthalif, Asan Gani (IIUM Press, 2011)
AC voltage supplies are commonly available in our residential or induSlIial envilllfllllent. however in consumer electronics the supply required is always DC voltage ~upply. Many devices employed for sensitive electronic operations. such as fine-luning and control. require an almost perfect DC voltage level which is normally obtained from Ihe available AC supply. However, mainlllining a perfectly constant voltage in the cUe of a supply is a challenging task to accomplish. The solution for this dilemma is 10 take thc AC voltage lind lectify it into a DC voltage supply (Scllaefer, 1%5; Baliga, 2010). To that end. many such circuits have been constructed. Here we explore a few rectifiers lIl1d discuss their mcthud ofopemtion